What are Universities For?: From Public Scholarship to the Engaged University - Sorgen, Jeremy (Journal for the study of religion, nature and culture, 2024)
"Public scholarship" uses academic research to help social groups respond to civic problems. Drawing on two distinct genealogies of public scholarship, I elaborate on an internal distinction between the "public intellectual" and "engaged scholar". Then, mapping this distinction onto my own research trajectory from theory to practice to engagement, I argue that scholarly focus on community practices can be as removed from public problem-solving as academic theory, whereas engaged scholarship is more accountable to the demands of justice. As "public scholarship" and its various cognates increasingly become corporate-speak in higher education, the scholars and communities who are the progenitors of engaged scholarship should lead the development of the "engaged university".